The Challenges of Practicum Courses on Online Learning - Helga Liliani Cakra Dewi; Chininta Rizka Angelia; Mujiono; Silvanus Alvin (Jurnal Komunikasi Profesional, 2023)
The Indonesian government encourages educational institutions to implement Online Learning (PJJ) through Law Number 20 of 2003. With the massive development of information and communication technology and the internet, now implementing PJJ system in educational institutions is a necessity. Hence, in 2020 Universitas Multimedia Nusantara established a Communication Study Program in PJJ. In teaching and learning activities, there are theoretical and practical course. This study aims to answer reaseach question about the challenges of practicum course that are implememted through the PJJ system. The method used in this study was Focus Group Discussion (FGD) with 40 students who were divided in several groups based on semester level. All FGD pratidipants had taken practicum coursed, namely the Digital Videography and Multimedia Laboratory. The result showed that the challenges faced in practicum courses are the differences of distance and time to complete group assignmenets among the students, the availability of learning support tools and facilities, and the updating of teaching material content. Alternative responses made by students are by subtituting practicum tools and utilizing social media such as Youtube and Instagram to enrich learning material. This study also found several expectations in practicum course, such as renewing learning materials by using language that is easier to understand, adjusting quiz questions, and increasing the frequency of synchronous virtual meetings.